Perceptions on Blackboard LMS: Voices from EFL Instructors - Sürüç Şen, Nur (My University, 2019)
Plentiful studies have been conducted to investigate the students’ perceptions of using the Blackboard Learning Management System since they are the ones who are provided with this system to increase the accessibility and availability of the educational materials (Liaw, 2007; Alhussain, 2017). On the other side of the coin, instructors play a crucial role in implementing the Blackboard LMS and eventually facing with some issues related to integration of the system. In particular, when EFL contexts are considered, features of Blackboard LMS might make positive contribution to improving accessibility and availability of educational resources. Although online learning management tools have grown interest in many previous research, it is crucial to expand the understanding the efficacy of them so that some drawbacks could be justified and ameliorated. Thus, the present study investigates perceived usefulness, satisfaction and some aspects of Blackboard Learning Management System to be modified for future use. The context of the study is a foundation university based in Turkey. In this study 28 EFL English teaching instructors participated. The findings of the study indicated that the instructors had positive perceptions under facilitative tools and facilitative aspects regarding Blackboard. On the other hand, the negative perceptions go under three categories: adaptation related, system related and implementation related. Regarding the second question, the highest level of attraction gathered from instructors belongs to the features such as posting announcements, assignments, uploading course files and giving feedback; whereas conducting online chat sessions, customizing the look of the course and creating course webpage have attracted the least level of attraction. Considering the third research question, 68% of the participants find Blackboard moderately easy to use and 60% of the participants think Blackboard is moderately useful. The results indicated that most of the participants find BB beneficial in accessing to students via e-mails, annoucements, chats. It encourages interactive and collaborative learning environment.Furthermore, findings yielded that the instructors need training in terms of using some features of Blackboard such as assigning writing tasks, giving online feedback. Interestignly enough, the interface has been commented as complicated and outdated. Thus, there is a need for a much more user-friendly version.